Le Livre e o Sintext: a simulação do sonho de Mallarmé através da poética digital de Pedro Barbosa - Fajardo, Luís Cláudio Costa (2009)
The project of dissertation Le Livre and the Sintext : The simulation of Mallarmé s dream through the digital poetics of Pedro Barbosa intends to evidence the connection between these two works, apart in time line but very intimate considering their poetic ideals: the unfinished Mallarmé s work Le Livre , ideated on XIX century and the digital text synthesizer, Sintext , anthological cyberliterary project, conceived by Pedro Barbosa and Manuel Torres in 2001. Mallarmé s masterpiece, the poem Dice Thrown Never Will Annul Chance , is probably the closest poetic experience of the Livre . This poem is, first of all, a poetic process, which the verses, distant one from the other and printed in various typefaces lead to a not lineal and limitless reading that offers the reader many entries and exits. The research approaches, at first, the development of cyber literature from hypertext s paradigm by going trough the multimedia digital poetics, the ergodic literature until focusing literary occurrences generated from a computer: the digital poetry, the generative literature and the hyperfiction, according to Pedro Barbosa´s proposal. In this trajectory, authors like Jay David Bolter, George Landow, Jacques Derrida. Levi Manovich, Lúcia Santaella, Giselle Bielguelman, Janet Murray, Aspen Arseth,Pedro Barbosa, Chris Funkenhouser, Rui Torres e Jorge Luiz Antônio are related. The dissertation proceeds with a presentation of the French poet s poetic work, and it proposes a comparison between the Sintext and the Livre , by coming into view the coincident points between these works, with the support of the work of the authors Maurice Blanchot , Jacques Scherer, Arlindo Machado, Octavio Paz, beside the others before mentioned. The climax of the project is a poetic experimentation in a digital medium wich Mallarmé s poem Dice Thrown Never Will Annul Chance is submitted to a text engine similar to the Sintext . The process is put into practice by a combinatorial operation with the verses of poem; it will enable innumerable possibilities of re-combining the verses, amplifying the meaning of the work and playing, by the digital poetics, the multiple and infinite book once conceived by Mallarmé